FoxK1 associated gene regulatory network in hepatic insulin action and its relationship to FoxO1 and insulin receptor mediated transcriptional regulation - Prasanna K.R. Allu; Maria Dafne Cardamone; Antonio S. Gomes; Alessandra Dall'agnese; Carly Cederquist; Hui Pan; Jonathan M. Dreyfuss; Sven Enerbäck; C. Ronald Kahn (Elsevier, 2023)
Objective: Insulin acts on the liver via changes in gene expression to maintain glucose and lipid homeostasis. This study aimed to the Forkhead box protein K1 (FOXK1) associated gene regulatory network as a transcriptional regulator of hepatic insulin action and to determine its role versus FoxO1 and possible actions of the insulin receptor at the DNA level. Methods: Genome-wide analysis of FoxK1 binding were studied by chromatin immunoprecipitation sequencing and compared to those for IR and FoxO1. These were validated by knockdown experiments and gene expression analysis. Results: Chromatin immunoprecipitation (ChIP) sequencing shows that FoxK1 binds to the proximal promoters and enhancers of over 4000 genes, and insulin enhances this interaction for about 75% of them. These include genes involved in cell cycle, senescence, steroid biosynthesis, autophagy, and metabolic regulation, including glucose metabolism and mitochondrial function and are enriched in a TGTTTAC consensus motif. Some of these genes are also bound by FoxO1. Comparing this FoxK1 ChIP-seq data to that of the insulin receptor (IR) reveals that FoxK1 may act as the transcription factor partner for some of the previously reported roles of IR in gene regulation, including for LARS1 and TIMM22, which are involved in rRNA processing and cell cycle. Conclusion: These data demonstrate that FoxK1 is an important regulator of gene expression in response to insulin in liver and may act in concert with FoxO1 and IR in regulation of genes in metabolism and other important biological pathways.